Protozoan-based biodiversity-safeguarding benchmark for triclosan in freshwater ecosystems - Kexin Yu; Jing Tang; Yuting Zhao; Pan Zhou; Jing Luo; Benchao Jiang; Xinying Su; Duu-Jong Lee; Xuming Pan; Li Wang (Ecotoxicology and Environmental Safety)
The global usage of triclosan (TCS)-containing disinfectants posed toxicity threats to freshwater biodiversity; at the same time, the ecological risk assessments based on Species Sensitivity Distribution (SSD) models overestimated the Predicted No-Effect Concentration (PNEC) of the TCS due to neglecting toxicity data for the secondary trophic level protozoa. This study conducted acute and chronic toxicity tests to obtain the toxicity parameters of Paramecium sp. (96 h-EC50=149 μg/L, 7 d-EC10=41 μg/L), Colpoda sp. (96 h-EC50=277 μg/L, 7 d-EC10=125 μg/L), Blepharisma sp. (96 h-EC50=277 μg/L, 7 d-EC10=640 μg/L), and Tetrahymena sp. (7 d-EC10=253 μg/L). A comprehensive acute and chronic toxicity dataset of TCS was established, including 64 freshwater species and 35 freshwater species. The relative tolerance test revealed that Paramecium sp. has a much higher sensitivity than the other tested protozoa, with a sensitivity between R. subcapitata (EC50=0.97 μg/L, EC10=2.5 μg/L) and D. magna (EC50=208.8 μg/L, EC10=46.2 μg/L)/D. rerio (LC50=428.8 μg/L, EC10=200 μg/L). The validated use of protozoa as an intermediate trophic level indicator of a multi-trophic SSD model enhanced the ecological relevance of the PNEC. The Z-score analysis confirmed the differential sensitivity across the biological groups; prioritizing sensitive species data during SSD construction prevents dominance by tolerant species, ensuring the derivation of conservative yet scientifically sound biodiversity-safeguarding thresholds. Incorporating protozoa toxicity data, the SSD model concludes TCS's short-term PNEC at 1 μg/L and long-term PNEC at 0.021 μg/L as freshwater biodiversity-safeguarding thresholds. This revised threshold supports the maintenance of species richness and ecological balance, providing robust scientific evidence for biodiversity conservation efforts.